2006
DOI: 10.1029/2004wr003773
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate attenuation in agricultural catchments: Shifting balances between transport and reaction

Abstract: [1] Simultaneous observations, across multiple spatial and temporal scales, are needed to understand the complex interactions between hydrological and biogeochemical processes in catchments and the primary controls on NO 3 À availability and mobility. This paper addresses these issues by using data collected from a detailed field experiment, carried out on two topographically different hillslopes (one steep and the other flat) located within an agricultural catchment in Western Australia. Continuous hydrometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
156
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 46 publications
3
156
1
Order By: Relevance
“…Harvey et al [2013] similarly found that the hyporheic zone was largely reaction limited in their study site. Ocampo et al [2006] applied the Da framework to hillslopes and riparian zones and found that the slope of the system acted as a major control on nutrient attenuation. The flatter hillslope, which had longer transport times, would consequently be reaction limited whereas the nitrate would behave similarly to a conservative tracer in the steep hillslope due to insufficient reaction time.…”
Section: Lansdown Et Almentioning
confidence: 99%
“…Harvey et al [2013] similarly found that the hyporheic zone was largely reaction limited in their study site. Ocampo et al [2006] applied the Da framework to hillslopes and riparian zones and found that the slope of the system acted as a major control on nutrient attenuation. The flatter hillslope, which had longer transport times, would consequently be reaction limited whereas the nitrate would behave similarly to a conservative tracer in the steep hillslope due to insufficient reaction time.…”
Section: Lansdown Et Almentioning
confidence: 99%
“…Denitrification, the biological conversion of NO 3 À to N 2 , is of importance in riparian zones and particularly in streambed sediments Hedin et al, 1998;Hill, 1996;Hill et al, 2000]. The extent to which biogeochemical processes influence contaminant transport depends on the relative rates of water transport and biological reactions [Brusseau et al, 1999;Gu et al, 2007;Ocampo et al, 2006]. Groundwater discharges during base flow and storms can have different residence times that can influence the extent of biological reactions .…”
Section: Introductionmentioning
confidence: 99%
“…These hydrological parameters influence catchment biogeochemistry (Ocampo et al, 2006;Oldham et al, 2013;Pinay et al, 2015;Tetzlaff et al, 2007), further increasing their value as 4 indicators and predictors of catchment-scale water quality and chemistry. Because these parameters are of great general interest they feature prominently in the inputs and outputs of many models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The mean transit time and whole stream residence time distribution are powerful metrics of catchment functioning, providing synoptic hydrological information such as water renewal time, heterogeneity of flowpaths, and overall water volume (Godsey et al, 2010;Hrachowitz et al, 2010; Marçais et al, 2015;McGuire and McDonnell, 2006;Van der Velde et al, 2012) . These hydrological parameters influence catchment biogeochemistry (Ocampo et al, 2006;Oldham et al, 2013;Pinay et al, 2015;Tetzlaff et al, 2007), further increasing their value as …”
mentioning
confidence: 99%